A Clinical Study of High Volume Camp Surgeries in a Tertiary Institute of Central India - Madhu Chanchlani (International Journal of Medical Research and Review, 2015)
Background: Blindness is one of the significant social problems in India with 7 million of the total 45 million blind people in the world residing in our country. If there is no change in the current trend of blindness, the number of blind persons in India would increase to 31.6 million in 2020. Apart from health and status of vision, there are many other socio-economic factors and perceptions, which influence the decision making of the people for getting operated for cataract. Productivity per individual surgeon/unit should be increased through a high volume, highquality cataract surgery approach to solve the problem of India’s curable blindness. As we are working in a Medical college hospital with experienced surgeons performing surgeries by Phaco-emulsification and utilizing the technique of manual small incision cataract surgery,planned study is undertaken to evaluate the results in a systematic manner.Aims and objectives: To analyze the outcome of cataract surgeries in camps in terms of duration of surgery, visual acuity, complications and their management.Material and Methods: It was a hospital-based, descriptive study. 3000 study subjects were recruited from the Department of Ophthalmology Chirayu medical College, Hospital from cataract camps, during three year period from December 2010 to December 2014.Results: In our study Mature cataract was seen in 41.2% cases.Intra operative complications were graded according to OCTET grading and was accounting for 5.30 %. Post-operative complications seen in our study was mild iritis 2.90%, severe iritis 2.28%, transient corneal oedema 4.20%, hypheama 1.17%, hypopyon 0.40%, residual cortex 1.20% and malposition of IOL seen in 3.30%. Levels of visual acuity after cataract surgery were categorized using the WHO guidelines of good outcome being 6/6 to 6/24, borderline outcome as 6/24 to 6/60 and poor outcome as <6/60 In the present study, the majority (89.5%) had a good outcome, (8.5 %) borderline, and (1.9)% cases had poor outcome, which implies that the visual outcome was very good.Conclusion - The study shows that high volume camp surgery plays a commendable role in transferring majority of elderly rural Indian population from the category of the blind and dependant to a group that is visually rehabilitated, independent, mobile and socially productive. A good choice of surgical technique, trained surgeons and paramedical personnel and good organizational setup can provide good visual outcome and increases the productivity per individual surgeon/unit to control blindness in developing world.